Ion channels as a therapeutic target for renal fibrosis - Yan, Peng; Ke, Ben; Fang, Xiangdong (Frontiers in Physiology, 2022)
Renal ion channel transport and electrolyte disturbances play an important role in the process of functional impairment and fibrosis in the kidney. It is well known that there are limited effective drugs for the treatment of renal fibrosis, and since a large number of ion channels are involved in the renal fibrosis process, understanding the mechanisms of ion channel transport and the complex network of signaling cascades between them is essential to identify potential therapeutic approaches to slow down renal fibrosis. This review summarizes the current work of ion channels in renal fibrosis. We pay close attention to the effect of cystic fibrosis transmembrane conductance regulator (CFTR), transmembrane Member 16A（TMEM16A）and other Cl channel mediated signaling pathways and ion concentrations on fibrosis, as well as the various complex mechanisms for the action of Ca2+ handling channels including Ca2+-release-activated Ca2+ channel (CRAC), purinergic receptor, and transient receptor potential (TRP) channels. Furthermore, we also focus on the contribution of Na transport such as epithelial sodium channel (ENaC), Na, K-ATPase, Na+-H+ exchangers, and K channels like Ca2+-activated K channels, voltage-dependent K channel, ATP-sensitive K+ channels on renal fibrosis. Proposed potential therapeutic approaches through further dissection of these mechanisms may provide new therapeutic opportunities to reduce the burden of chronic kidney disease.